Human development under fiscal, financial, and environmental constraints: Evidence from SAARC economies - Jainendra Kumar Verma; Kothapeta Lakshman (Public and Municipal Finance, 2026)
Type of the article: Research ArticleAbstractThe present study investigates the macroeconomic determinants of human development in eight South Asian Association for Regional Cooperation (SAARC) economies during the period 1990–2023, with special emphasis on the roles of public debt, economic growth, financial development, and environmental degradation. A fixed-effects estimation with Driscoll–Kraay robust standard errors and Dumitrescu–Hurlin panel causality tests on an unbalanced panel dataset of 204 observations is used to test the long-run relationships and dynamic interactions among the variables. The results indicate that economic growth and financial development are important and robust determinants of human development. The findings underscore the importance of raising income and deepening finance for the improvement of human capabilities. The effects of public debt on development depend on fiscal governance and the productive use of borrowed resources. Public debt does not have a significant independent effect once well-known econometric problems are accounted for. Environmental degradation is a serious threat to human development and a complex illustration of the link between industrial transformation and sustainability in developing economies. The study highlights the importance of integrated policies in the SAARC economies for promoting inclusive growth, financial inclusion, fiscal prudence, and environmental sustainability.